Sidewalk flowers - Lawson, JonArno (Groundwood Books/House of Anansi Press, 2015)
A little girl collects wildflowers while on a walk with her distracted father. Each flower becomes a gift, and whether the gift is noticed or ignored, both giver and recipient are transformed by their encounter. This wordless picture book, conceived by award-winning poet JonArno Lawson and beautifully brought to life by illustrator Sydney Smith, is an ode to the importance of small things, small people and small gestures.